Spatio-temporal comparison of pertussis outbreaks in Olmsted County, Minnesota, 2004–2005 and 2012: a population-based study. Issue 5 (19th May 2019) - Wi, Chung-Il; Wheeler, Philip H; Kaur, Harsheen; Ryu, Euijung; Kim, Dohyeong; Juhn, Young
Abstract : Objective: Two pertussis outbreaks occurred in Olmsted County, Minnesota, during 2004–2005 and 2012 (5–10 times higher than other years), with significantly higher incidence than for the State. We aimed to assess whether there were similar spatio-temporal patterns between the two outbreaks. Setting: Olmsted County, Minnesota, USA Participants: We conducted a population-based retrospective cohort study of all Olmsted County residents during the 2004–2005 and 2012 outbreaks, including laboratory-positive pertussis cases. Primary outcome measure: For each outbreak, we estimated (1) age-specific incidence rate using laboratory-positive pertussis cases (numerator) and the Rochester Epidemiology Project Census (denominator), a medical record-linkage system for virtually all Olmsted County residents, and (2) pertussis case density using kernel density estimation to identify areas with high case density. To account for population size, we calculated relative difference of observed density and expected density based on age-specific incidence. Results: We identified 157 and 195 geocoded cases in 2004–2005 and 2012, respectively. Incidence was the highest among adolescents (ages 11 to <14 years) for both outbreaks (9.6 and 7.9 per 1000). The 2004–2005 pertussis outbreak had higher incidence in winter (52% of cases) versus summer in 2012 (53%). We identified a consistent area with higher incidence at the beginning (ie, first quartile) of two outbreaks, but it was inconsistent for later quartiles. The relative difference maps for the two outbreaks suggest a greater role of neighbourhood population size in 2012 compared with 2004–2005. Conclusions: Comparing spatio-temporal patterns between two pertussis outbreaks identified a consistent geographical area with higher incidence of pertussis at the beginning of outbreaks in this community. This finding can be tested in future outbreaks, and, if confirmed, can be used for identifying epidemiological risk factors clustered in such areas for geographically targeted intervention.